EVALUATION OF AIRPORT RAIL SERVICES BASED ON MINIMUM SERVICE STANDARDS (SPM) - Dinda Sekar Selni Prawardani; Imam Basuki (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2024)
The Yogyakarta government's decision to construct the Yogyakarta International Airport (YIA) was prompted by the limited capacity of Adisutjipto Airport, which could only accommodate 1.2 million passengers. In reality, the number of passengers exceeded five times its capacity due to congested flight schedules and inadequate airport facilities. Since 2020, flights have been redirected to YIA, as stated on the official Adisutjipto Airport website. The airport's distant location from the city center influenced the development of mass transportation, particularly the direct rail connection between YIA and Yogyakarta city center. The YIA Airport Train Station began operations in October 2021, prompting the need for an evaluation of service facilities within the train and at the YIA Airport Station. This study aims to assess the extent to which services within the Airport Train and the YIA Airport Station meet minimum service standards and to innovate scheduling to improve passenger satisfaction. The Government has established the Minimum Service Standards for People Transportation by Train, covering safety, security, reliability, comfort, convenience, and equality. Evaluation is conducted through qualitative methods, including direct observation and an online questionnaire for primary data collection. The evaluation results indicate that several service facilities do not meet standards, such as the absence of toilets and prayer rooms in the station, a shortage of seating in waiting areas, inappropriate temperatures inside the train, and the need for additional departure schedules aligned with flights. The questionnaire reflects passengers' expectations for improved facilities and scheduling. This study proposes enhancements to facilities and train scheduling as steps toward improving service quality in the Airport Train and YIA Airport Station.